Pengembangan dan Pengelolaan Adat Budaya Melalui Pembentukan Rancangan Peraturan Desa Dongko, Kabupaten Trenggalek - Muhammad Marcellino Putra Putra Syadila; Nela Erdianti; Ravenzka Ash Shafa Chikita Jasmine; Yana Indawati (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The Trenggalek Regency is home to Dongko Village, which is found in the Dongko District. Dongko Village is one of the potential Tourism Villages because of the rich variety of its traditions and histories. Dongko's cultural customs are an integral part of the village's identity and must be safeguarded in both their physical and legal manifestations if the village is to continue to grow and be managed effectively. Empirical study was conducted, which depicts an investigative process present in all areas of social life, including volunteer work. The term "empirical research" refers to a kind of study in which hard data and proof are gathered by direct observation and experimentation. The author conducted the study by making personal observations in the wild. Due to a lack of specificity in Law 12 of 2011, the provisions of Law 6 of 2014 pertaining to villages are consulted in order to determine how to construct Village Regulations. The Village Regulation is a cornerstone of village life, as it governs the day-to-day operations of the village government and the community at large. In line with article 24 of Law No. 6 of 2014, the Perdes product stands as a symbol of the spread of democracy to the grassroots level. As a result, the PKM (Community Service) Team in Dongko Village, Dongko District, Trenggalek Regency uses the Legislation work program with one of its legal products, namely the drafting of Village Regulations, to restore the Village Regulations in accordance with the needs of the village communities.